1995
DOI: 10.1055/s-2008-1058927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Hearing Preservation in Acoustic Tumor Surgery

Abstract: The goals in acoustic tumor surgery are total tumor removal and preservation of neurologic function, with primary emphasis placed on preserving the anatomic integrity and function of the facial nerve. The combination of improved surgical technique and advances in intraoperative neurophysiologic monitoring methods have made these goals attainable."2 With the advent and use of magnetic resonance imaging (MRI), it is now possible to find smaller tumors in patients who still have normal or near-normal hearing thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…2,3,5–11 One of the most frequently investigated potentially prognostic preoperative factors is the ABR. Authors including Nadol et al 3 and Rastogi et al 11 found no relationship between ABR results and the possibility of hearing preservation. However Glasscock et al 2 and Ogawa et al 5 reported that a severe abnormality on ABR was an indicator that hearing preservation attempts would likely be futile and that ABR should be used as a selection criteria for surgical approach.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2,3,5–11 One of the most frequently investigated potentially prognostic preoperative factors is the ABR. Authors including Nadol et al 3 and Rastogi et al 11 found no relationship between ABR results and the possibility of hearing preservation. However Glasscock et al 2 and Ogawa et al 5 reported that a severe abnormality on ABR was an indicator that hearing preservation attempts would likely be futile and that ABR should be used as a selection criteria for surgical approach.…”
Section: Discussionmentioning
confidence: 98%
“…The resultant data are useful to counsel the patient, establish realistic expectations, and guide the decision making process regarding surgical approaches. Several tumor and patient characteristics have been reported with variable effectiveness to provide useful prognostic information regarding postoperative hearing, including presenting symptoms, gender, preoperative tumor size, pure‐tone average (PTA) hearing sensitivity, speech reception threshold (SRT) levels, word recognition scores, acoustic reflex thresholds, auditory brainstem response (ABR) waveforms, otoacoustic emission (OAE) waveforms, and electronystagmography (ENG) 2–11 . In particular, preoperative ABR results have been extensively studied and many authors have noted that absent ABR is associated with poor postoperative hearing prognosis 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the RS approach, several articles have proposed prognostic factors (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), with widely variable conclusions (Table 6). In descending order of importance, tumor size, preoperative hearing status, extension in the fundus, tumor origin, preoperative ABR, patient's age, and sex have all been proposed as factors for predicting hearing preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar correlations were not confirmed by a study by Slattery et al 19 and Brackmann et al, 20 as well as the results of the present analyses. Rastogi et al analyzed the influence of preoperative hearing thresholds at 4,000 Hz and 8,000 Hz on surgery-related hearing status in patients operated on due to VS. 21 However, no statistically significant correlations were demonstrated.…”
Section: Pure-tone Audiometrymentioning
confidence: 91%
“…Rohit et al also found no correlation between SDS and surgery-related hearing loss. 18 Rastogi et al conducted a study including 44 VS patients which demonstrated no influence of SRT or SDS on postoperative hearing status 21 .…”
Section: Speech Audiometrymentioning
confidence: 99%